Selective SERS Sensing Modulated by Functionalized Mesoporous Films - López Puente, Vanesa (2015)
A hybrid material comprising metal nanoparticles embedded in functionalized mesoporous thin films was constructed, and its use as a selective SERS-based sensor was demonstrated. The presence of specific functional groups in the pore network allows control over the surface chemistry of the pores, tuning the selectivity for specific molecules. Amino-functionalized hybrid mesoporous thin films were used in a proof of concept experiment, to discern the presence of methylene blue (MB) in mixtures with acid blue (AB), with no need for any sample pretreatment step. Selective detection of MB was possible through entrapment of AB in the mesoporous matrix, based on its high affinity for amino groups. The sensor selectivity can be tuned by varying the solution pH, rendering a pH responsive surface and thus, selective SERS-based sensing. The developed sensors allow specific detection of molecules in complex matrixes.